Filmes na tela hemisférica: Fulldome, animação e experimentação - Vitor Amaro Lacerda (2022)
This work investigates, based on references from film theory and history, audiovisual production for hemispherical screens, in particular films in Fulldome format, an immersive audiovisual projection standard used in planetariums and other domic architecture environments. Based on the concept of dispositif, the course of the research was oriented towards the outline of a broad cartography of Fulldome that sought to highlight the interrelationships between its historical, technological, architectural, institutional and discursive dimensions. At first, the bibliographic dialogue with the field of media archeology supported the search for other media and artistic forms that are inscribed in its historical constitution, or that resonate recurrent conceptions in Fulldome films, beyond the paradigms of modern planetariums activities. Then, we sought to understand how, together, the elements that make up the dispositif strategically concur to support a regime of spectatorship that ideally favors a reverential attitude in relation to the experience of audiovisual enjoyment under the dome, which is confirmed in discursive level through an analysis of the films, their main strands and commonplaces. Having established a panorama of this form considered as a manifestation of the “expanded cinema”, we also sought to discuss possible lines of experimentation that, recognizing the heterogeneity of the device, can contribute to its diversification into different aspects of production, especially with regard to the techniques, processes for producing and the poetics of the animated image. Thus, it is expected to offer systematic contributions to the theoretical insertion of hemispheric audiovisual forms in the field of film theory, understood in its diversity of manifestations and exhibition configurations; as well as the formation of a reference base that can stimulate, encourage and support eventual production projects in this field.